2019
DOI: 10.24248/eahrj.v3i1.593
|View full text |Cite
|
Sign up to set email alerts
|

Unpacking Loss to Follow-Up Among HIV-Infected Women Initiated on Option B+ In Northern Tanzania: A Retrospective Chart Review

Abstract: Background: In 2014, Tanzania adopted the Option B+ policy for the prevention of mother-to-child transmission of HIV (PMTCT), which stipulates lifelong antiretroviral therapy (ART) for HIV-infected pregnant, postpartum and breastfeeding women, irrespective of CD4 count or WHO clinical staging. Loss to follow-up (LTFU) during pregnancy and the postpartum period may undermine the effectiveness of Option B+. Factors associated with no follow-up (NFU) care, may differ from those associated with LTFU at later time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 21 publications
1
14
1
Order By: Relevance
“…[25, 26] The study conducted Kilimanjaro region on the predictors of postpartum HIV care engagement among women in the PMTCT program, suggested strengthening the social support network system by engaging treatment supporters in HIV care. [13, 16, 18, 27, 28] Therefore, findings from this study cement the importance of engaging treatment supporters not only in engaging mothers to care but also to ensure that their babies receive the…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…[25, 26] The study conducted Kilimanjaro region on the predictors of postpartum HIV care engagement among women in the PMTCT program, suggested strengthening the social support network system by engaging treatment supporters in HIV care. [13, 16, 18, 27, 28] Therefore, findings from this study cement the importance of engaging treatment supporters not only in engaging mothers to care but also to ensure that their babies receive the…”
Section: Discussionmentioning
confidence: 74%
“…The finding is consistent with findings of past studies in Northern Tanzania, which revealed a high loss to follow-up after the first two months post-delivery as one of the setbacks in the implementation of Option B+. [15, 16] Does this have to do with insufficient knowledge about the Option B+ cascade of services until after 18 months? Probably they thought that the DBS-PCR 1 test results were confirmatory and there was no need for another test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Tanzania adopted Option B+ in 2013, and studies have demonstrated subsequent increases in the rates of HIV diagnosis and linkage to care. 2 , 3 However, a meta-analysis of studies in Africa showed that retention in PMTCT care is lower than in the general population of people living with HIV (PLWH), threatening the effectiveness of PMTCT programs and the goals of the Option B+ protocol. 4 Multiple studies conducted in East Africa have identified HIV stigma as a primary factor influencing retention in PMTCT care.…”
Section: Introductionmentioning
confidence: 99%
“…1 Tanzania adopted Option B+ in 2013, and studies have demonstrated subsequent increases in the rates of HIV diagnosis and linkage to care. 2,3 However, a meta-analysis of studies in Africa showed that retention in PMTCT care is lower than in the general population of people living with HIV (PLWH), Stigma impacts retention to PMTCT in a variety of ways. 5 During pregnancy and the postpartum period, WLHIV in Tanzania describe feeling uniquely vulnerable to stigma, particularly in the form of fear of abandonment or mistreatment by their partner or the loss of other key social supports.…”
mentioning
confidence: 99%